Survival study on teeth after successful endodontic surgical retreatment: influence of crown height, root length, crown-to-root ratio and tooth type - Daniele Angerame; Matteo De Biasi; Massimiliano Lenhardt; Lorenzo Bevilacqua; Vittorio Franco (Ariesdue, 2018)
Aim: To assess the influence of the crown height, root length, crown-to-root ratio, and tooth type on the survival of teeth subjected to surgical endodontic retreatment and classified as periapically healed. Methodology: A single operator performed endodontic microsurgery interventions between 2008 and 2018 on teeth with refractory apical periodontitis. The present analysis selected the teeth classified as "complete periapical healing" according to the scale suggested by Molven. The postoperative periapical radiographs and those taken at the last recall visit were analysed by two independent calibrated examiners, who measured crown height and root length in a blind manner. The crown-to-root ratio was calculated as the ratio of the two variables. The level of inter- and intra-operator agreement was tested with Bland-Altman plots with 95% limits of agreement. An independent statistician conducted a survival analysis using Kaplan-Meier plots and a log-rank test (α = 0.05) to assess the significance of the differences among the subgroups defined by the following criteria: (a) crown height <median vs. >median; (b) root length <median vs. >median; (c) crown-to-root ratio <1 vs. >1; (d) crown-to-root ratio <median vs. >median; (e) single-rooted teeth vs. multi-rooted teeth. Results: At the end of the analysis, 42 patients were evaluated, each one contributing to the study with a single tooth. The mean follow-up period was 4.2 ± 2.4 years. Survival estimates were significantly improved for the teeth with roots longer than 8 mm, in comparison with that with shorter roots (p < 0.05). There were no statistically significant differences among the remaining considered subgroups. Conclusions: Under the conditions of this retrospective study, teeth with longer residual roots after apical surgery exhibited better chances of survival when compared to teeth with roots shorter than 8 mm. The other considered variables did not seem to affect the survival of apically resected teeth. Riassunto: Obiettivi: Valutare l'influenza dell'altezza coronale, della lunghezza radicolare, del rapporto corona-radice e del tipo di dente sulla sopravvivenza di denti sottoposti ad apicectomia e classificati come guariti a livello periapicale. Materiali e metodi: Un singolo operatore ha svolto interventi di endodonzia microchirurgica dal 2008 al 2018 su denti con paradentite periapicale refrattaria. La presente analisi ha selezionato i denti classificati come «guarigione radicolare completa» secondo la scala di Molven. Le radiografie periapicali postoperatorie e quelle scattate all'ultima visita di controllo sono state analizzate da due operatori indipendenti e calibrati che hanno misurato in cieco altezza coronale e lunghezza radicolare. Il rapporto corona-radice è stato calcolato dal rapporto delle due variabili. Il livello di concordanza inter- e intra-operatore è stato testato con i diagrammi di Bland-Altman con limiti di concordanza al 95%. Uno statistico indipendente ha svolto un'analisi di sopravvivenza usando le curve di Kaplan-Meier e test Log-Rank (α = 0.05) per verificare la significatività delle differenze tra i sottogruppi definiti dai seguenti criteri: altezza coronale<mediana vs. >mediana; lunghezza radicolare<mediana vs. >mediana; rapporto corona-radice<1 vs. >1; rapporto corona-radice<mediana vs. >mediana; denti monoradicolati vs. pluriradicolati. Risultati: Al termine dell'analisi il campione era costituito da 42 pazienti, seguiti per 4,2±2,4 anni, ciascuno dei quali ha contribuito allo studio con un dente. Le stime di sopravvivenza sono risultate significativamente migliori per i denti con radici più lunghe di 8 mm nel confronto con quelle di lunghezza inferiore (p < 0.05). Non sono emerse ulteriori differenze statisticamente significative dal confronto tra gli altri sottogruppi considerati. Conclusioni: Nelle condizioni del presente studio retrospettivo, elementi dentari con radici residue lunghe a seguito di chirurgia apicale hanno mostrato migliori probabilità di sopravvivenza, paragonati a elementi con radici più corte di 8 mm. Le altre variabili testate non hanno influenzato la sopravvivenza dei denti sottoposti a resezione apicale. Keywords: Crown-to-root ratio, Late failure, Retrospective study, Survival analysis, Surgical endodontic retreatment, Parole chiave: Analisi di sopravvivenza, Fallimento tardivo, Rapporto corona-radice, Ritrattamento endodontico chirurgico, Studio retrospettivo